2005
DOI: 10.2463/mrms.4.35
|View full text |Cite
|
Sign up to set email alerts
|

ADC Mapping of Benign and Malignant Breast Tumors

Abstract: DWI has the potential in clinical appreciation to detect malignant breast tumors and support the evaluation of tumor extension. However, the benign proliferative change remains to be studied as it mimics the malignant phenomenon on the ADC map.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
237
7
20

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 310 publications
(295 citation statements)
references
References 29 publications
31
237
7
20
Order By: Relevance
“…Many studies report absolute threshold ADC values to differentiate benign and malignant lesions (6,7,(11)(12)(13)(14). However, all authors recommended other threshold ADC values, ranging from 1.10Á10 À3 to 1.60Á10 À3 mm 2 /s.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies report absolute threshold ADC values to differentiate benign and malignant lesions (6,7,(11)(12)(13)(14). However, all authors recommended other threshold ADC values, ranging from 1.10Á10 À3 to 1.60Á10 À3 mm 2 /s.…”
Section: Discussionmentioning
confidence: 99%
“…Many different strategies have been proposed to increase the specificity such as calculating pharmacokinetic contrast parameters (4), T2*-weighted perfusion imaging (5) and MR spectroscopy (5). A promising adjunct MRI technique is diffusion-weighted imaging (DWI) (6)(7)(8)(9)(10)(11)(12)(13)(14)(15). In DCE Breast MRI, lesions are characterized based on morphology, internal enhancement, and kinetic enhancement pattern (16,17).…”
Section: In Recent Years Dynamic Contrast Enhanced (Dce)mentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluation of metastatic disease is of prime importance, particularly in MIBC, although there are no studies evaluating the use of DWI for this purpose. Whole body DWI is an emerging technique currently being used for other cancers, and Woodhams et al reported that DWI has the potential in clinical appreciation to examine malignant breast tumours and support the assessment of tumour infiltration [37]. Clinical diagnosis of BC stage is currently done mostly using computed tomography (CT); however, Lista et al showed that CT could not adequately differentiate the degree of bladder wall infiltration and tumour stage in BC, and its ability to detect invasion to adjacent organs is limited [27].…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion-weighted imaging DWI is a type of MRI sequence that captures the diffusion movement of water molecules, and is reportedly effective in distinguishing between benign and malignant tumors in the endometrium 10 . Subsequent reports indicate that DWI is also effective in distinguishing between benign and malignant tumors in various areas, and in identifying localized extension [11][12][13][14][15][16][17][18][19][20] . We therefore sought to evaluate the effectiveness of DWI in identifying localized extension of uterine body cancer.…”
Section: Introductionmentioning
confidence: 99%